Proposed Marketing Strategies for Dots & Dotz Ice Cream in Achieving Sales Target - Vimala, Khema; Purwanegara, Mustika Sufiati (The Indonesian Journal of Business Administration, 2013)
Everyone knows what its ice cream, both from small children to the elderly, like ice cream. Of opportunity and that opportunity, formed Dots&Dotz ice cream that sold ice cream with a palette concept. So in 1 palette consists of 3-8 cones with a variety of flavors in accordance with the wishes of consumers. The business issue is every outlet in Bandung cannot reach the target. This study used questionnaires, depth interviews, and analysis of the questionnaire results. From the analysis, shown that the level of awareness Dots&Dotz very low and this results from a lack of promotion. In addition, the root of the problem that occurred was the perception assessment Dots&Dotz undervalued importance of consumer ratings will be ice cream. Based on existing problems, the researchers propose some solutions for Dots&Dotz in terms of internal repair company. One of them is by changing the positioning and target consumers, creating a classical conditioning so that consumers can understand the meaning of the concept Dots&Dotz. This change will work well when Dots&Dotz promotion and also how to choose the right promotional media to provide that information. In addition, the authors also provide inputs, such as budget for promotion, and promotion planning time.Â Keywords: Brand Awareness, Marketing Mix, Classical Condition, Promotion